Effect of Combining Ultrasound with Osmotic Pre-treatment on Osmotic Characteristics of Pomelo Peel - Xavier, Navis Ryan; Abdullah, Norazlin; Muhammad, Norhayati; Mohd Rozalli, Norazatul Hanim (Journal of Science and Technology, 2017)
Pre-treatment of food greatly manipulates the food processing applications and techniques that enhance the quality characteristics of food thus producing a wide array of preserved foods. This research aims to investigate the effect of application of radiating ultrasound waves, coupled with the presence osmotic dehydration as pre-treatment, on water loss (%) and solid gain (%) in pomelo (Citrus grandis) fruit peels. Pomelo peels were immersed in three different osmotic concentrations (0%, 50% and 100%) of food grade sucrose solutions, in the presence of ultrasound waves with three varying ultrasound bath temperatures (30°C, 50°C and 70°C) at two different immersion times (10 minutes and 30 minutes). The values for water loss and solid gains were calculated from the values of moisture content (initial and final) and weight (initial and final). At constant lowest immersion time (10 minutes), decreasing ultrasound bath temperature and increasing osmotic concentration resulted in greater water loss (%), at the same time, resulted in the lesser solid gain (%). This result dictated that solid gain fluctuations are not affected by the percentage of osmotic concentration. Pre-treatment with 10 minutes immersion time, 30°C ultrasound bath temperature and 100% osmotic concentration employed the ideal value of both water loss and solid gain. This indicates that low immersion time and temperature with greatest osmotic concentration dehydrates the pomelo peels to preserve the fruit via ultrasound assisted osmotic dehydration process.